Patai's Chemistry of Functional Groups 2014
DOI: 10.1002/9780470682531.pat0871
|View full text |Cite
|
Sign up to set email alerts
|

1,1‐Dihydroperoxides

Abstract: Gem ‐dihydroperoxides ( g ‐DHPs), often referred to as 1,1‐dihydroperoxides, are a class of molecules of interest because of their reactivity as well as their utility as synthetic reagents and intermediates. This review begins with a listing of previous reviews and commercially available g ‐DHPs, followed by a brief discussion of safety and regulatory issues. The properties of g ‐DHPs are then overviewed, with an emphasis on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…This lower stabilization in peroxide-bearing cation should shape the potential energy surface for the equilibrium between the cationic species involved in the acid catalyzed formations of endo- and exocyclic peroxides and hydroperoxides from carbonyl compounds and H 2 O 2 . These processes open synthetic access to a surprising diversity of oxygen-containing functionalities including geminal bis-hydroperoxides, geminal bis-peroxides, tetraoxanes, cyclic triperoxides, tricyclic monoperoxides, and ozonides …”
Section: Resultsmentioning
confidence: 99%
“…This lower stabilization in peroxide-bearing cation should shape the potential energy surface for the equilibrium between the cationic species involved in the acid catalyzed formations of endo- and exocyclic peroxides and hydroperoxides from carbonyl compounds and H 2 O 2 . These processes open synthetic access to a surprising diversity of oxygen-containing functionalities including geminal bis-hydroperoxides, geminal bis-peroxides, tetraoxanes, cyclic triperoxides, tricyclic monoperoxides, and ozonides …”
Section: Resultsmentioning
confidence: 99%
“…This approach to the preparation of peroxides benefits from the broad availability of such starting materials and from the great reactivity of nucleophilic peroxide oxygen toward carbonyl compounds. These reactions opened synthetic access to many important classes of peroxides, such as geminal bis-hydroperoxides, geminal bis-peroxides, tetraoxanes, cyclic triperoxides, and tricyclic monoperoxides . However, peroxides containing the 1,2,4-trioxolane moiety (i.e., secondary ozonides) have been traditionally obtained using ozone.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the reaction of ketones or aldehydes with H 2 O 2 and hydroperoxides serves as one of the main synthetic approaches to organic peroxides. Although many publications describe reactions of hydrogen peroxide and monoketones, the problem of peroxidation selectivity in the presence of several reactive centers has not found a general solution. For β-dicarbonyl compounds, this issue has been successfully addressed only in a small number of literature reports. It was shown that β-diketones can be transformed into 1,2,4,5-tetraoxanes, , whereas δ-diketones can be converted into 1,2,4-trioxolanes (ozonides) (Scheme ).…”
Section: Introductionmentioning
confidence: 99%